Pluralitas dalam Menjaga Toleransi di Tana Toraja - Yunus Yunus; Mukoyyaroh Mukoyyaroh (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2022)
Philosophically, Tana Toraja can be described as a representation of local wisdom and cosmological awareness about the unity between humans, the universe and God. In Toraja society, in one family and even in one house, adherents of different religions can be found, but they remain in harmony and peace thanks to the customs and philosophy of Tongkonan local wisdom. Studies related to culture in society cannot be measured using data in the form of numbers, because researchers use qualitative methods with ethnographic (realist) and phenomenological approaches. Aluk Todolo's belief in establishing religious harmonization in Tana Toraja is very important because diversity will never be able to build a dynamic and integrative social order if it is not managed properly. Moderation values such as tolerance are important to be instilled especially for the Toraja people, namely, learning to live in differences, building mutual trust, maintaining mutual understanding, upholding mutual respect, being open in thinking, appreciation and interdependence, conflict resolution, and reconciliation. non-violence.